Paracrine Engineering of Human Explant-Derived Cardiac Stem Cells to Over-Express Stromal-Cell Derived Factor 1α Enhances Myocardial Repair. (21st April 2016) - Tilokee, Everad L.; Latham, Nicholas; Jackson, Robyn; Mayfield, Audrey E.; Ye, Bin; Mount, Seth; Lam, Buu-Khanh; Suuronen, Erik J.; Ruel, Marc; Stewart, Duncan J.; Davis, Darryl R.
Abstract: First generation cardiac stem cell products provide indirect cardiac repair but variably produce key cardioprotective cytokines, such as stromal-cell derived factor 1α, which opens the prospect of maximizing up-front paracrine-mediated repair. The mesenchymal subpopulation within explant derived human cardiac stem cells underwent lentiviral mediated gene transfer of stromal-cell derived factor 1α. Unlike previous unsuccessful attempts to increase efficacy by boosting the paracrine signature of cardiac stem cells, cytokine profiling revealed that stromal-cell derived factor 1α over-expression prevented lv-mediated "loss of cytokines" through autocrine stimulation of CXCR4+ cardiac stem cells. Stromal-cell derived factor 1α enhanced angiogenesis and stem cell recruitment while priming cardiac stem cells to readily adopt a cardiac identity. As compared to injection with unmodified cardiac stem cells, transplant of stromal-cell derived factor 1α enhanced cells into immunodeficient mice improved myocardial function and angiogenesis while reducing scarring. Increases in myocardial stromal-cell derived factor 1α content paralleled reductions in myocyte apoptosis but did not influence long-term engraftment or the fate of transplanted cells. Transplantation of stromal-cell derived factor 1α transduced cardiac stem cells increased the generation of new myocytes, recruitment of bone marrow cells, new myocyte/vessel formation and the salvage of reversibly damaged myocardium to enhance cardiac repair after experimental infarction.